All in good fun: governing camp experiences through discourses of 'good' and 'fun'. Issue 2 (4th March 2019) - Baker, Mandi; Fullagar, Simone; O'Brien, Wendy
ABSTRACT: Summer camps have been conventionally associated with the positive development of individual character through the promotion of recreational 'fun.' However, popular narratives obscure more critical questions concerning the power-knowledge relations that have shaped the provision of summer camp fun as a significant site of child development in Canadian culture. In this article we examine how camp counsellors mobilise particular discourses about the benefits, or 'good', and 'fun' of camp to govern themselves and the campers that are in their care. We draw on Foucauldian notions of governmentality to problematise that which is often assumed as the 'truth' of camp experiences. We discuss how the 'good' of camp often draws on psy-discourses and those of entrepreneurial selves to improve or add value to campers' lives. Additionally, 'fun' discourses and practices can work to produce manageable and docile campers. We conclude the article by identifying the implications of the research for developing a critical approach to the management of young staff who work to provide a broad range of recreational experiences where benefits and fun are promised.